Push-out test of waste sawdust-based steel-concrete – Steel composite sections: Experimental and environmental study. (December 2022) - Sharba, Amjad Ali K.; Hason, Mahir M.; Hanoon, Ammar N.; Qader, Diyar N.; Amran, Mugahed; Abdulhameed, Ali A.; Al Zand, Ahmed W.
Abstract: Considering their cost and strength benefits over traditional reinforced concrete, steel–concrete–steel (SCS) structural systems have become increasingly popular. The ultimate strength, ductility index, failure modes, cost, environment, and energy absorption capacities of SCS filled with sawdust concrete were explored in this study to better understand the impact of using SCS in modern structural projects. Wood chips were employed as an infill material to minimize the section's weight and expense. Push-out monotonic loading was used to inspect the mechanical characteristics of six SCS samples. One sample was built using the typical normal-weight concrete core to serve as a standard, while the other samples were made with changed core materials by partially replacing the fine aggregate with sawdust. The discovered failure modes are explained and analyzed, with the ultimate strength, ductility, and energy absorption index. The research suggests that recycled lightweight infill concrete has a slightly lesser effect on the performance of the SCS than conventional concrete (less than 10 %). It was observed that the percentage of sawdust had an impact on the specimens' compressive strengths, with the strength decreasing from 65 to 48 MPa as the sawdust levels climbed from 7.27 % to 29.63 %. The energy absorption of the SCS sawdust concrete was lower than the control sample. Conversely, the ductility index of the control specimen was higher than those of waste wood SCS samples. The results also revealed that using sawdust material has a positive impact on the economic and environmental systems.